Emotional and Interactional Prosody across Animal Communication Systems: A Comparative Approach to the Emergence of Language - Filippi, Piera (Frontiers in Psychology, 2016)
Across a wide range of animal taxa, prosodic modulation of the voice can express emotional information and is used to coordinate vocal interactions between multiple individuals. Within a comparative approach to animal communication systems, I hypothesize that the ability for emotional and interactional prosody (EIP) paved the way for the evolution of linguistic prosody - and perhaps also of music, continuing to play a vital role in the acquisition of language. In support of this hypothesis, I review three research fields: i) empirical studies on the adaptive value of EIP in nonhuman primates, mammals, songbirds, anurans and insects; ii) the beneficial effects of EIP in scaffolding language learning and social development in human infants; iii) the cognitive relationship between linguistic prosody and the ability for music, which has often been identified as the evolutionary precursor of language.